النَّشاط الإصلاحي عند الشَّيخ محمَّد خير الدِّين في منطقته بسكرة - زيد, مليكة (جامعة الوادي - University of Eloued, 2022)
في هذا البحث قمنا بإلقاء الضوء على أحد الشخصيات البارزة في الحركة الإصلاحية في مدينة بسكرة ، وهو محمد خير الدين خلال الفترة الاستعمارية التي واجهتها جمعية العلماء المسلمين الجزائريين. وقد شهدت جهودا ثمينة تهدف إلى تكوين الفرد الصالح لتحرير البلاد من الجهل والتخلف. كما يهدف هذا البحث إلى التعرف على شخصيته وإبراز أهم أنشطته الإصلاحية في بسكرة. ومن هنا خلص البحث إلى أن الفترة الاستعمارية جعلت هذه الشخصية قوية وحازمة. وقد كان شخصية مؤثرة أنقذت الهوية العربية والإسلامية للجزائريين. In this research, we shed light on one of the outstanding figures of the reform movement in the city of Biskra which is Muhammad Khair al-Din during the colonial period which was confronted by the Association of Muslim Scholars. He witnessed valuable efforts aimed at forming a good individual for liberating the country from ignorance and backwardness. This research aims at identifying his personality and highlighting his most important reform activities in Biskra. Hence, the research concluded that the colonial period made this personality strong and determined. He was an influential figure that saved the Algerians' Arabic and Islamic identity.
مقال
Keywords: النشاط الإصلاحي ، الشيخ محمد خير الدين ، بسكرة